Oracle9i DBA JumpStart - Bryla, Bob (SYBEX, 2003)
Oracle9i DBA JumpStart gives you the solid grounding you need to approach Oracle certification with confidence: Introduction to relational database concepts Using basic SQL*Plus and iSQL*Plus commands Understanding Oracle database functions Using multiple tables Restricting, sorting, and grouping data Creating and maintaining a database Using SQL*Plus reporting techniques Creating and maintaining database objects Setting up users and managing security Configuring optimization Creating backups Troubleshooting